AI Ethics and Ethics in AI- some crucial differences and development possibilities - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
AI ethics could be defined as the set of guiding principles that all actors using or developing AI should or must use in order to ensure artificial intelligence technology is developed and used responsibly and wisely. This means taking a safe, secure, humane, and environmentally friendly approach to artificial intelligence (in the further text: AI) and its using, as well as using of results given by AI.            If we take AI Ethics, shortly explained as earlier, as external ethical guidance for users of AI, should  there be also – internal ethical guidance for the AI itself, as set of internal moral values that will lead AI in its development and application in everyday use ? The questions we are dealing in this paper are: What is the ethical minimum, as a set of ethical principles that every user or person who participates in the development of AI must have, in order for the use of AI to be safe and wise? On what values ​​should this external ethical minimum rest, and does it, once established, have to remain the same or can it be improved and add/subtract values, in accordance with the exploration of the possibilities provided by AI itself? And is it possible for AI to develop a separate consciousness, with the help of its creators, which will protect it from unmoral   attempts by users with bad intentions?
Keywords: AI, ethics, internal morality, external morality